New developments in energy transfer and transport studies in relativistic laser-plasma interactions - Norreys, P; Green, J; Lancaster, K; Robinson, A; Scott, R; Perez, F; Schlenvoight, H; Baton, S; Hulin, S; Vauzour, B; Santos, J; Adams, D; et al. (2010)
Two critical issues related to the success of fast ignition inertial fusion have been vigorously investigated in a co-ordinated campaign in the European Union and the United States. These are the divergence of the fast electron beam generated in intense, PW laser-plasma interactions and the fast electron energy transport with the use of high intensity contrast ratio laser pulses. Proof is presented that resistivity gradient-induced magnetic fields can guide fast electrons over significant distances in (initially) cold metallic targets. Comparison of experiments undertaken in both France and the United States suggests that an important factor in obtaining efficient coupling into dense plasma is the irradiation with high intensity contrast ratio laser pulses, rather than the colour of the laser pulse itself. © 2010 IOP Publishing Ltd.